Digital Parenting Mediation for Children with Mild Intellectual Disability: Predictors of Restrictive and Active Strategies - Annisa May Syarah Nasution; Yeni Irma Normawati; Rezi Akbar Zarnazi (Asosiasi Asesmen Pendidikan (AAP), 2025)
Children with mild intellectual disability are particularly vulnerable to online exploitation, cyberbullying, and excessive screen exposure due to limitations in critical reasoning and social comprehension. This descriptive correlational study explored parental mediation patterns among families whose children regularly use digital devices. A culturally adapted 25 item questionnaire (20 mediation items + 4 parental self efficacy items) was used. This research was analyzed using ANOVA. The findings indicate significant differences in parental mediation, with restrictive strategies more pronounced among families with longer gadget use and active mediation more prevalent among parents with higher education and greater self-efficacy. Overall, parental belief in their ability to manage technology, combined with educational factors and children's device-use habits, shaped the form and intensity of mediation. The findings underscore the need for digital parenting interventions that reinforce parental confidence and encourage a more balanced shift from restrictive control toward supportive, communicative, and proactive mediation strategies.